2012
DOI: 10.1111/j.1939-1676.2011.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Plasma Metabolites, Hormones, and mRNA Abundance of Adipose Leptin and Hormone‐Sensitive Lipase in Ketotic and Nonketotic Dairy Cows

Abstract: Background: Ketosis is an important metabolic disorder of dairy cows during the transition period. There have been many reports on the etiology of ketosis in periparturient cows, but little is known about its molecular etiology.Objectives: The objective of this study was to clarify the status of fat mobilization and mRNA abundance of leptin and hormone-sensitive lipase in cows with spontaneous clinical ketosis.Animals: Ten ketotic Holstein cows and 10 nonketotic Holstein cows were used as the experimental anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…and high energy demands play crucial roles in the pathogenesis of ketosis [24]. Our results revealed that BHBA and acetone were higher in K1, consistent with the findings of other researchers [25]. In amino acid metabolism, the anabolism and catabolism of proteins need to be in dynamic balance to maintain normal physiological functions.…”
Section: Discussionsupporting
confidence: 81%
“…and high energy demands play crucial roles in the pathogenesis of ketosis [24]. Our results revealed that BHBA and acetone were higher in K1, consistent with the findings of other researchers [25]. In amino acid metabolism, the anabolism and catabolism of proteins need to be in dynamic balance to maintain normal physiological functions.…”
Section: Discussionsupporting
confidence: 81%
“…If the cows had little clinical symptoms and high plasma BHBA concentrations (> 1.20 mmol/L), they were considered to have SK. If the cows had no clinical signs and normal plasma BHBA concentrations (< 1.00 mmol/L), they were considered normal controls (NC) [3,4]. Within 12 h of calving, whole first-morning blood samples were collected and immediately centrifuged at 1400 × g for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Ketosis can be clinically indicated by elevated blood concentrations of ketone bodies, such as β-hydroxybutyrate (BHBA), acetoacetate, and acetone [7][8][9]. Many studies have found that BHBA is a predominant and stable blood ketone body in ruminant ketosis [4,10], which, therefore, has been widely used for clinically diagnosing and classifying ketosis in dairy cows [11].…”
Section: Introductionmentioning
confidence: 99%